Towards holistic radiation protection. Lessons from the literatures - Zainuddin, Zainul Ibrahim (IIUM Press, 2018)
The effects of radiation on man and his health had been noticed since the early years after the discovery of X-rays. These biological concerns were more commonly known as “radio-sensitiveness” in the early publications. Later, the term radiation protection was introduced to express the need for protective measures to be promoted, formulated, implemented, evaluated and sustained to reduce the biological effects associated with radiation exposure. The principles of radiation protection were then supported with the concepts of justification, ALARA and “Benefits against the risks”. But these could not ensure that the application of radiation protection has been optimized. Amidst the technological advancements associated with radiation based imaging modalities in healthcare for more than 120 years, those advancements have yet to be able reduce the impact of these modalities being a source of risks upon the more beneficial role as a diagnostic tool. This paper reports a review on radiation protection from articles indexed in an online database. Considering that the titles of the articles contain the core subject matter that a publication carries, data were retrieved on those titles with the term “radiation protection”. Publications from 2008 to middle of November 2017 and aligned to Medicine and Health professions were included for further elaborations. The data were classified into four subject areas; education and training, administration and organization, practice and research. Discussions within each classification and their individual sub-classifications, supported by selected publications to the classification, highlight the importance of the particular subject area to the overall concept of radiation protection. Lessons learnt from the classifications could provide the necessary guidance on how one should adopt and adapt the concept of radiation protection holistically. The discussions that are presented are seen within the professional obligation in adhering to the principles of radiation protection.